2019
DOI: 10.1111/tmi.13332
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health knowledge among adolescents in eight sites across sub‐Saharan Africa

Abstract: objective To examine knowledge of menstruation, HIV and STIs other than HIV across eight sites in SSA to develop effective programmatic interventions enabling adolescents to achieve positive SRH as their transition to adulthood.methods We combine data from eight Health and Demographic Surveillance Sites across sub-Saharan Africa, from an adolescent-specific survey that included 7116 males and females age 10-19 years old. We provide pooled and site-specific estimates from multiple analytic models examining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 31 publications
7
35
1
2
Order By: Relevance
“…This finding contradicts the result described by studies conducted in Nigeria, where females are more likely to have HIV-knowledge than that of the males [40]. Additionally, the study in Sub Saharan Africa (SSA) uncovered that females have a positive association with having better knowledge than males [41]. Contrary to this, sex did not affect having HIV knowledge in the study done among university students in the United Arab Emirates (UAE) [42].…”
Section: Discussioncontrasting
confidence: 79%
“…This finding contradicts the result described by studies conducted in Nigeria, where females are more likely to have HIV-knowledge than that of the males [40]. Additionally, the study in Sub Saharan Africa (SSA) uncovered that females have a positive association with having better knowledge than males [41]. Contrary to this, sex did not affect having HIV knowledge in the study done among university students in the United Arab Emirates (UAE) [42].…”
Section: Discussioncontrasting
confidence: 79%
“…These projections present a message that youth access to health care will be an important aspect of the pursuit of Universal Health Coverage (Manyeh et al 2018). In other words, the pressure on health systems to meet the important, but currently unmet youth healthcare needs will be unescapable (Finlay et al 2020). Sexual and reproductive health (SRH) is one of (if not) the most important healthcare needs of the youth.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is also found that family structure is important to the development of sexual behaviour of young teenagers. For this particular research, the effect of family structure is one of the important elements to be studied in more details because the participants who are involved in this study come from two different family structures living with two-parent families and living with single-parent families (Finlay et al, 2020). Therefore, this research sought to investigate the youth's perspectives of the topic of teenage pregnancy and sexuality, as well as to investigate the current educational efforts to teach sexuality to youths in schools, and the influence of family structure on youth perception of teenage pregnancy, sexuality and sex education.…”
Section: Literature Reviewmentioning
confidence: 99%